Cognitive and neuropsychiatric effects of noradrenergic treatment in Alzheimer's disease: systematic review and meta-analysis. Issue 10 (5th July 2022) - David, Michael C B; Del Giovane, Martina; Liu, Kathy Y; Gostick, Benjamin; Rowe, James Benedict; Oboh, Imafidon; Howard, Robert; Malhotra, Paresh A
Abstract : Background: Dysfunction of the locus coeruleus-noradrenergic system occurs early in Alzheimer's disease, contributing to cognitive and neuropsychiatric symptoms in some patients. This system offers a potential therapeutic target, although noradrenergic treatments are not currently used in clinical practice. Objective: To assess the efficacy of drugs with principally noradrenergic action in improving cognitive and neuropsychiatric symptoms in Alzheimer's disease. Methods: The MEDLINE, Embase and ClinicalTrials.gov databases were searched from 1980 to December 2021. We generated pooled estimates using random effects meta-analyses. Results: We included 19 randomised controlled trials (1811 patients), of which six were judged as 'good' quality, seven as 'fair' and six 'poor'. Meta-analysis of 10 of these studies (1300 patients) showed a significant small positive effect of noradrenergic drugs on global cognition, measured using the Mini-Mental State Examination or Alzheimer's Disease Assessment Scale—Cognitive Subscale (standardised mean difference (SMD): 0.14, 95% CI: 0.03 to 0.25, p=0.01; I 2 =0%). No significant effect was seen on measures of attention (SMD: 0.01, 95% CI: −0.17 to 0.19, p=0.91; I 2 =0). The apathy meta-analysis included eight trials (425 patients) and detected a large positive effect of noradrenergic drugs (SMD: 0.45, 95% CI: 0.16 to 0.73, p=0.002; I 2 =58%). This positive effect was still present following removal of outliers to account for heterogeneity across studies. Discussion: Repurposing of established noradrenergic drugs is most likely to offer effective treatment in Alzheimer's disease for general cognition and apathy. However, several factors should be considered before designing future clinical trials. These include targeting of appropriate patient subgroups and understanding the dose effects of individual drugs and their interactions with other treatments to minimise risks and maximise therapeutic effects. PROSPERO registeration number: CRD42021277500.